The Relationship Between State and District Content Standards:Issues of Alignment, Influence and Utility - Dutro, Elizabeth; Valencia, Sheila (Education Policy Analysis Archives, 2004)
At the core of standards-based reform are content standards–statements about what students should know and be able to do. Although it is state standards that are the focus of much public attention and consume substantial resources, many local school districts have developed their own content standards in the major subject areas. However, we know very little about the role state standards have played in local standards efforts. In this article we report on a study of the relationship between state and local content standards in reading in four states and districts. Through interviews with key personnel in each state, and district and analyses of state and local content standards in reading, we explored the alignment between state and district content standards, the path of influence between the two, and the role of high-stakes tests in state and districts reform efforts. Our findings suggest that alignment had multiple meanings and that state standards had differential utility to districts, ranging from helpful to benign to nuisance. This wide variability was influenced by the nature of the standards themselves, the state vision of alignment and local control, districts’ own engagement and commitment to professional development, and student performance on high-stakes tests. We explore implications for the future of content standards as the cornerstone of standards-based reform and argue that states must promote district ownership and expand accountability if state content standards are to have any relevance for local efforts to reform teaching and learning.